Sensitisation to outdoor and indoor fungi in atopic dermatitis patients and the relation to the occurrence of food allergy to peanuts and walnuts - Čelakovská, Jarmila; Bukač, Josef; Ettler, Karel; Vaneckova, Jaroslava; Ettlerova, Kvetuse; Krejsek, Jan (Mycoses, 2018)
The aim of this study is the evaluation of the relation between the sensitisation to outdoor and indoor fungi and allergy to peanuts and walnuts in atopic dermatitis patients aged 14 years and older. The complete dermatological and allergological examinations were performed in all included patients; the occurrence of food allergy to peanuts and walnuts was recorded (specific IgE, skin prick test, history of allergic reaction) and the sensitisation to mixture of outdoor fungi and indoor fungi was also examined (skin prick test, specific IgE). The statistical evaluation of the relation between the sensitisation to outdoor and indoor fungi and the occurrence of food allergy to peanuts and walnuts was performed; 329 patients were included in the study, 110 men and 219 women, the average age 26.8 years. The sensitisation to outdoor fungi was recorded in 91 patients (28%), the sensitisation to indoor fungi was recorded in 61 patients (18.5%), the occurrence of food allergy to peanuts was confirmed in 90 (27%) patients and to walnuts in 121 (36.7%) patients. We confirmed, that patients suffering from sensitisation to outdoor fungi suffer significantly more from food allergy to peanuts and walnuts. The significant relation between the sensitisation to indoor fungi and food allergy to peanuts and walnuts was not confirmed.
Keywords: Female; Immunization; Adolescent; imunizace; mužské pohlaví; mladý dospělý; Immunoglobulin G; Fungi; Humans; dospělí; Dermatitis, Atopic; atopická dermatitida; Arachis; potravinová alergie; lidé; Juglans; ženské pohlaví; imunoglobulin G; houby; alergeny; Food Hypersensitivity; Young Adult; Adult; Allergens; Male; mladiství